The influence of total solids content and initial pH on batch biohydrogen production by solid substrate fermentation of agroindustrial wastes. - Robledo-Narváez, Paula N.; Muñoz-Páez, Karla M.; Poggi-Varaldo, Hector M.; Ríos-Leal, Elvira; Calva-Calva, Graciano; Ortega-Clemente, L. Alfredo; Rinderknecht-Seijas, Noemí; Estrada-Vázquez, Carlos; Ponce-Noyola, M. Teresa; Salazar-Montoya, J. Alfredo (Journal of Environmental Management, 2013)
Hydrogen is a valuable clean energy source, and its production by biological processes is attractive and environmentally sound and friendly. In México 5 million tons/yr of agroindustrial wastes are generated; these residues are rich in fermentable organic matter that can be used for hydrogen production. On the other hand, batch, intermittently vented, solid substrate fermentation of organic waste has attracted interest in the last 10 years. Thus the objective of our work was to determine the effect of initial total solids content and initial pH on H production in batch fermentation of a substrate that consisted of a mixture of sugarcane bagasse, pineapple peelings, and waste activated sludge. The experiment was a response surface based on 2 factorial with central and axial points with initial TS (15–35%) and initial pH (6.5–7.5) as factors. Fermentation was carried out at 35 °C, with intermittent venting of minireactors and periodic flushing with inert N gas. Up to 5 cycles of H production were observed; the best treatment in our work showed cumulative H productions (ca. 3 mmol H/g) with 18% and 6.65 initial TS and pH, respectively. There was a significant effect of TS on production of hydrogen, the latter decreased with initial TS increase from 18% onwards. Cumulative H productions achieved in this work were higher than those reported for organic fraction of municipal solid waste (OFMSW) and mixtures of OFMSW and fruit peels waste from fruit juice industry, using the same process. Specific energetic potential due to H in our work was attractive and fell in the high side of the range of reported results in the open literature. Batch dark fermentation of agrowastes as practiced in our work could be useful for future biorefineries that generate biohydrogen as a first step and could influence the management of this type of agricultural wastes in México and other countries and regions as well.